Herd Behavior in Financial Markets : An Experiment with Financial Market Professionals - Cipriani, Marco; Guarino, Antonio (Washington, D.C. : International Monetary Fund, 2008)
We study herd behavior in a laboratory financial market with financial market professionals. We compare two treatments, one in which the price adjusts to the order flow so that herding should never occur, and one in which event uncertainty makes herding possible. In the first treatment, subjects herd seldom, in accordance with both the theory and previous experimental evidence on student subjects. A proportion of subjects, however, engage in contrarianism, something not accounted for by the theory. In the second treatment, the proportion of herding decisions increases, but not as much as theory suggests; moreover, contrarianism disappears altogether.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet